AUTOMATED STORAGE AND RETRIEVAL SYSTEM AN ALTERNATIVE FOR LOGISTIC TRANSFORMATION TECHNOLOGY: A CASE STUDY - Ardhi Bebi Laksono (President University, 2021)
This research was taken at one of the mechanical engineering companies produces customize spare parts, special purposed machinery, automation system integrator and robotic installation. The company has problem high cost operation warehouse, need space expanding production line, stockopname problem, picking failure, high cycle time operation, logistic efficiency, and inventory cost. These problems have impact to company performance which need cost down, increase efficiency and productivity with minimum defect. The data has shown company needs additional 157m2 to expanding new line, has 4% picking defect, there is 200 million operational cost over, 150sec cycle time, 7% lost part and risk cyber data security. Due to the importance of the problem, the company needs to evaluate and solve the problem which has impact to company performance, especially in the warehouse. DMAIC (Define Measure Analyze Improve and Control) approach is applied to comprehensively explore the problem and comes out with alternatives solution. Two alternatives were developed. The criteria for selection used were i.e. cost; accuracy, security, safety, productivity, cycle time, and minimize defect It was concluded that the application of automated storage and retrieval system (ASRS) was selected as it dominates in many aspects compare to expanding the current one. This implementation of ASRS approved that this new system answers the current warehouse problem